Work Environment And Job Satisfaction Affect Perfomance Through The Achievement Motivation Of The Teachers Of SMA 6 Tangerang - Chrestian Prasetyo Hadi; Muhammad Ali Iqbal (Dinasti International Journal of Management Science, 2023)
This study aims to determine the influence of the work environment and job satisfaction mediated by the achievement motivation to the performance of teachers of SMA 6 Tangerang. This research uses a quantitative approach with a survey method. The total respondents are 54 teachers of SMA 6 Tangerang, with saturated sampling techniques. The data collection method uses a questionnaire with a Likert scale of 1 to 5. Data analysis using descriptive analysis Structural Equation Model-Partial Least Square (SEM-PLS) software version 3.0. The results showed that the work environment has a positive effect but has an insignificant effect on teacher performance. Job Satisfaction has a positive and significant effect on teacher performance. Achievement Motivation has a positive and significant effect on teacher performance. Achievement Motivation mediates the work environment and job satisfaction to the teacher perfomance.